2018
DOI: 10.18087/cardio.2018.1.10083
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Biomarkers of Cardiovascular Diseases

Abstract: Резюме В настоящее время нет сомнений в том, что важную роль в развитии и патогенезе сердечно-сосудистых заболеваний (ССЗ) играют микроРНК. Обнаружение существенных изменений уровня экспрессии данных молекул при различных заболеваниях позволяет рассматривать их в качестве потенциальных биомаркеров заболеваний человека, в том числе сердечной недостаточности. Изучение механизмов взаимосвязи между ССЗ и уровнем экспрессии различных микроРНК, а также установление их точных взаимосвязей с генами является актуальной… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…65 Alteration in levels of miRNA have been implicated in conditions such as cervical cancer, ovarian cancer, endometriosis and CVDs. 6668 Studies have shown differential expression of miRNA in women with PCOS compared with controls, suggesting a potential role of miRNA in PCOS. 69,70 Chen et al have extensively discussed the role of miRNA in PCOS.…”
Section: Origins Of Androgen Excess In Pcos and Pre-receptor Androgenmentioning
confidence: 99%
“…65 Alteration in levels of miRNA have been implicated in conditions such as cervical cancer, ovarian cancer, endometriosis and CVDs. 6668 Studies have shown differential expression of miRNA in women with PCOS compared with controls, suggesting a potential role of miRNA in PCOS. 69,70 Chen et al have extensively discussed the role of miRNA in PCOS.…”
Section: Origins Of Androgen Excess In Pcos and Pre-receptor Androgenmentioning
confidence: 99%
“…Therefore, finding markers for the early diagnosis of HCC remains the focus of current relevant research. miRNA has become a promising biomolecule for the diagnosis, prognosis, and treatment of tumours with the development of miRNA research [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are essential contributors to the modulation of CVD by targeting various genes (23,24). miR-383 is involved in various cellular processes related to the development of various diseases, such as generation of malignancies and cerebral ischemia (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%